2019
DOI: 10.1042/bsr20191454
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms of MTHFR, TCN2, RNF213 with susceptibility to hypertension and blood pressure

Abstract: Methylenetetrahydrofolate reductase gene (MTHFR), transcobalaminII (TCN2) and ring finger protein 213 (RNF213) are related to homocysteine (Hcy) level and are of great significance for hypertension. We aimed to evaluate the associations of MTHFR (rs1801133, rs1801131, rs9651118), TCN2 (rs117353193) and RNF213 (rs9916351) with hypertension and blood pressure (BP). A total of 953 patients with hypertension and 1103 controls were enrolled. Genotyping was performed by Taqman. Logistic regression analysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition, MMD is also frequently accompanied with hypertension (17). A possible reason for this is that changes in RNF213 expression can result in increased blood pressure, which aggravates RNF213 gene silencing upregulates transforming growth factor β1 expression in bone marrow-derived mesenchymal stem cells and is involved in the onset of Moyamoya disease intracranial hemodynamic disorders further and induce the formation of 'smoky' blood vessels (18,19). A homozygous variant of RNF213 is considered to be the most pathogenic and was found to be significantly associated with severe manifestations of MMD (20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MMD is also frequently accompanied with hypertension (17). A possible reason for this is that changes in RNF213 expression can result in increased blood pressure, which aggravates RNF213 gene silencing upregulates transforming growth factor β1 expression in bone marrow-derived mesenchymal stem cells and is involved in the onset of Moyamoya disease intracranial hemodynamic disorders further and induce the formation of 'smoky' blood vessels (18,19). A homozygous variant of RNF213 is considered to be the most pathogenic and was found to be significantly associated with severe manifestations of MMD (20).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the T allele was associated with a higher risk of hypertension in Taiwanese ( 48 ), Chinese ( 47 , 50 , 77 ), Indians ( 78 ), and Australian Caucasians ( 52 ), and the TT genotype in Moroccans ( 51 ). Nonetheless, the variant was not significantly associated with hypertension in Algerians ( 79 ), South Africans ( 80 ), Chinese ( 54 , 81 ), Danish ( 53 ), Caucasians ( 55 ), Japanese ( 56 ), Black Africans ( 76 ), Latinos ( 76 ), Sri Lankans ( 76 ), and Indians ( 76 ). We believe that the conflicting results between our study and those previously reported could, in part, be due to differences in ethnicities, sample sizes, and study designs.…”
Section: Discussionmentioning
confidence: 95%
“…Studies about some populations in the three northeastern provinces of China have found that polymorphisms in the MTHFR genes A1298C and C677T are not significantly associated with hypertension ( Liu et al, 2019 ). In this case-control study of oil workers in Karamay, Xinjiang, adjusting for confounding factors, mutant genes at the A1298C polymorphism and the C677T polymorphism of the MTHFR gene were found to be susceptible genotypes for hypertension, which is consistent with the findings of and Alghasham et al (2012) .…”
Section: Discussionmentioning
confidence: 99%